Anticipated stigma and quality of life among people living with chronic illnesses. - Earnshaw, Valerie A; Quinn, Diane M; Park, Crystal L (Chronic illness, 2012)
We examined the process by which anticipated stigma relates to quality of life among people living with chronic illnesses. We hypothesized that stress, social support and patient satisfaction mediate the relationships between three sources of anticipated stigma and quality of life.
Keywords: Adolescent; Adult; Aged; Anticipation, Psychological; Chronic Disease; Female; Humans; Male; Middle Aged; Patient Satisfaction; Quality of Life; Social Stigma; Social Support; Stereotyping; Stress, Psychological